(untitled) (Archive of Conferences, 2021)
Special attention is paid to the training of qualified and competitive personnel for the labor market by improving the professional education system, which is considered important in the development of the state and society in the global environment, on the basis of advanced foreign experience, introducing the stages of primary, secondary and secondary special professional education. In particular, Japan, the United Kingdom, Germany, the United States, the Russian Federation, Canada, Korea, Switzerland, Hungary, Turkey and China are the leading scientific centers of the developed countries of the world and the theoretical and practical issues of creative competence in educational institutions.